Rancang Bangun Robot Berkaki Enam Menggunakan Pola Gerak Tripod Gait - Dhia Farhan; Sujono Sujono; Nazori AZ (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
In this study, a six-legged robot (hexapod) was designed to detect the presence of a victim by interpreting the shape of an orange cube and passing through various obstacles such as a broken road, a downhill road with rocks, a flat road with rocks, a muddy road with marshes and a stair climb using the Gait Tripod movement pattern. The hexapod is designed to have a size of 31.8 cm x 27.4 cm x 18 cm. The robot consists of 18 servo motors that each foot uses 3 servos, 2 HC-SR04 ultrasonic sensors right and left as the sensor of the distance between the robot and the wall, the TCS230 color sensor as the detection of victims and the Arduino Mega2560 as the microcontroller that regulates the work of the system on the robot. When the robot finds the victim, the LED lights up to indicate the victim has been found. On obstacles a straight path without obstacles and boundary walls up to 120 cm can move forward at a speed of 18.6 seconds with a deviation of 3.6 cm, at a distance of 80 cm has a speed of 12.8 seconds with a deviation of 11.9 cm, and at a distance of 40 cm has a speed of 7.1 seconds with a deviation of 15.9 cm. On broken road obstacles the robot can pass with a speed of 20.7 seconds, on downhill road obstacles with rocks it can pass with a speed of 20.3 seconds, on flat road obstacles with rocks it can pass with a speed of 19.3 seconds, on muddy road obstacles with muddy media it can pass with a speed of 17.5 seconds, but on stair climbing obstacles the robot fails to pass the obstacles.